Why Is It So Difficult to Contribute to Social Inclusion Through Vocational Education and Training? - Markus Maurer; Mahboob Morshed; Ognen Spasovski (Nordic Journal of Comparative and International Education, 2022)
This paper compares “recognition of prior learning” (RPL) schemes in four countries, to find out the impact of VET policy reforms on social inclusion. The study finds that RPL schemes have only made limited contributions to social inclusion in these countries, for the following reasons: firstly, there are challenges in upper secondary VET, which, in all four countries, requires a substantial level of general education and transversal competencies, on which the key educational policy actors are not willing to compromise. Secondly, some countries used RPL to provide access to non-formal qualifications. Still, such schemes were only successful when those non-formal qualifications were already well-established in society and the labour market (prior to having been made accessible through RPL). The article argues that, for RPL to contribute more to social inclusion, schemes need to be less complicated and should also include complementary education and training provisions for all those who lack work experience in sectors where access to employment depends on certain qualifications.